PERLINDUNGAN HUKUM PELAPOR TERSANGKA (JUSTICE COLLABORATOR) DALAM PERKARA PIDANA KORUPSI - Arief Wisnu Wardhana (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
Justice Collaborator interpreted initiative to provide information / information about the crime comes from within the self-perpetrator acknowledging his actions and then assisting law enforcement officials by providing information related to the crime committed and the involvement of other principal actors of the nature of the criminal network, although There is a difference between the two terms above there are similarities that both are perpetrators of criminal acts. The term Justice Collaborator in the Indonesian criminal justice system is a novelty, explicitly the Criminal Procedure Code (KUHAP), the Corruption Act and other Law not regulating the Justice Collaborator and in accordance with developments in enforcement practices Criminal law which is then received attention and subsequently regulated in the positive law of Indonesia.Justice Collaborator initiative to provide information / information about the crime comes from within the perpetrator of his conscience acknowledge his actions done and then assist law enforcement officials by providing information relating to criminal acts Conducted and the involvement of other key actors in the criminal network, although there is a difference between the two terms above there are similarities that both are the perpetrators of the crime.Therefore the need for integration of the criminal justice system so that suat U the system seeks to balance the protection of interests of both the interests of the state, society and individuals, including the interests of criminals and victims of crime. This is in line with the ultimate goal of criminal politics, namely the protection of society within the framework of wisdom to achieve social welfare or social politics. With the criminal justice system, the protection of human dignity and human dignity in the criminal process. It can be said that the wisdom to achieve the goals of the welfare of the community which is the goal of the welfare state law must be supported by the policy of criminal law enforcement through the criminal justice system primarily through formal criminal law.According to Muladi integrated criminal justice system is synchronization or alignment of structural, substantial and culture. The three things are interrelated and affect. The functioning of an integrated and well-defined criminal justice system is determined to what extent these three synchronizations work. If there is a weakness in one of the system work component will affect the other components in the integrated system. The criminal justice system as described in the KUHAP is an integrated criminal justice system laid out on the principle of